Development of a biomaterial associated with mesenchymal stem cells and keratinocytes for use as a skin substitute. (November 2015) - Steffens, Daniela; Mathor, Monica B; Santi, Bruna TS; Luco, Dayane P; Pranke, Patricia
Aim: The present study has aimed to produce a cutaneous substitute, bringing together stem cells (mesenchymal stem cells) and keratinocytes, and an electrospun biomaterial.Materials & methods: Three groups of scaffolds were studied: group 1, poly-dl -lactic acid (PDLLA); group 2, hydrolyzed PDLLA (PDLLA/NaOH) and group 3, PDLLA/Lam – a PDLLA/NaOH scaffold linked to laminin protein. They were characterized by physicochemical and biological parameters.Results: As a result, the scaffolds presented well-formed and randomly distributed fibers. Group 3 showed the greatest hydrophilic characteristics. Group 1 showed a greater degradation rate after 14 days. Groups 2 and 3 presented molecular weight of about 40–50 Da. In general, group 3 showed the best results concerning cell adhesion and viability.Conclusion: This study associated two revolutionary fields, stem cells and nanotechnology, for use in regenerative medicine.